Britain at the polls 2010 - Allen, Nicholas (Political scientist); Bartle, John, 1968- (Sage, 2011)
The Britain at the Polls series always asks and answers, often with new insights the key questions about British general elections. And few elections in living memory pose as many big questions as that of May 2010. - Martin Kettle, The Guardian. 'For decades Britain at the Polls has given us high quality insights into British elections. This latest edition is the most significant and intriguing of all: an excellent cast of contributors provide a vivid and accessible presentation of evidence with an engaging clarity of writing and depth of analysis. It should prove invaluable not only for acad.